P175 Single centre experience of the real-life impact of pirfenidone on lung function in patients with idiopathic pulmonary fibrosis. (15th November 2016) - Rathnapala, A; Fries, A; West, Y; Ho, LP; Hoyles, RK
Abstract : Introduction: Idiopathic pulmonary fibrosis (IPF) is a progressively destructive lung disease that culminates in respiratory failure and death. Trials have demonstrated that treatment of IPF patients with Pirfenidone reduces %FVC decline, improves progression-free survival and significantly reduces the risk of all-cause mortality at 1 year. Our anecdotal experience is that a small proportion of patients show improvement of %FVC with treatment. Objectives: To assess the proportion of patients in an ILD specialist centre that improve, stabilise or decline in their %FVCs on Pirfenidone treatment. Methods: In this retrospective study patients with IPF diagnosed according to the ATS/ERS guidelines at the ILD MDT, who were commenced and continued on Pirfenidone for >6 months were included. Data was derived from the clinical records of the Oxford IPF clinic. Results: 100 patient records were analysed and 31 were excluded (n = 15 <6 months' therapy, n = 5 inadequate data, n = 2 death <1 month, n = 9 other). 58 (84.1%) male, 11 (15.9%) female; 38 (55.1%) had Definite IPF, 31 (44.9%) Probable IPF. Six months after commencing Pirfenidone (n = 69 patients), 5 (7.25%) experienced significant (>10%) and 9 (13.04%) experienced marginal (5–10%) improvement in %FVC, 33 (47.83%) showed stability (−5% to 5% change %FVC), 10 (14.49%) showed marginal decline (−5% to −10%) and 12 (17.39%) showed significant (>10%) decline in %FVC. After one year of Pirfenidone (n = 44 patients), 3 (6.8%) showed significant and 5 (11.4%) showed marginal improvement, 18 (40.9%) showed stability, 11 (25%) showed mild and 7 (15.9%) showed significant decline of %FVC. After 2 years of treatment (n = 15 patients), 1 (6.7%) showed significant and 3 (20%) showed mild improvement, 4 (26.7%) showed stability, 3 (20%) showed mild and 4 (26.7%) showed significant decline of the %FVC. Among 8 patients who had improvement in %FVC at one year, 6 were males, 6 had definite IPF, median age 77 years (68 – 84) and the median FVC was 73.5% predicted (66 – 79). Conclusions: Real-life use of Pirfenidone shows clear slowing of decline in the %FVC, whereas a clinically significant subset show improvement in FVC. Potentially the beneficial effect is lost after 22–24 months, although small numbers limit this analysis.